2021
DOI: 10.1101/2021.03.06.434206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latency structure of BOLD signals within white matter in resting-state fMRI

Abstract: Previous studies have demonstrated that BOLD signals in gray matter in resting-state functional MRI (RSfMRI) have variable time lags. We investigated the corresponding variations of signal latencies in white matter within 1393 subjects (both sexes included) from the Brain Genomics Superstruct Project. We divided the dataset into ten equal groups to study both the patterns and reproducibility of latency estimates within white matter. We constructed time delay matrices by computing cross-correlation functions be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Similar to previous study on WM using completely independent dataset (Guo et al 2021a), results from this dataset also exhibited network-level lead/lag relationships, suggesting existence of dominant direction of signal propagations. We further applied linear mixed-effect analysis on the mean latencies of the off-diagonal blocks to investigate the main effect of stages on the variations of each mean latency.…”
Section: -B)supporting
confidence: 85%
See 4 more Smart Citations
“…Similar to previous study on WM using completely independent dataset (Guo et al 2021a), results from this dataset also exhibited network-level lead/lag relationships, suggesting existence of dominant direction of signal propagations. We further applied linear mixed-effect analysis on the mean latencies of the off-diagonal blocks to investigate the main effect of stages on the variations of each mean latency.…”
Section: -B)supporting
confidence: 85%
“…K-means, a clustering technique, was applied on voxel-wise FC matrix within WM to obtain RSNs. A path of signal propagation, dominated by the direction from the inferior to the superior, was identified by performing latency analysis on WM RSNs, similar to previous study on a different dataset with large cohort of youngsters (Guo et al 2021a) at the resolution of 8 RSNs. Hence, in this study, the whole WM were parcellated into 8 clusters, as shown in Figure 8-A, by applying K-means on group-level FC matrix consisting of paired voxels of N2 group where the most subjects were included.…”
Section: Latency Among Rsns In Relation To Different Sleep Stagesmentioning
confidence: 86%
See 3 more Smart Citations